2015
DOI: 10.1111/echo.12961
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Left Atrial Deformation Parameters and Their Prognostic Impact in Patients with Pathological Left Ventricular Hypertrophy: Analysis by Speckle Tracking Echocardiography

Abstract: This study suggested that the EMT-diff could discriminate patients with a high risk of cardiac events among patients with pathological LV hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
(34 reference statements)
8
26
0
Order By: Relevance
“…This is in accordance with other STE studies in HTN patients with LV hypertrophy [12,13]. Some authors even showed an early impairment of LA reservoir function in the absence of LV hypertrophy [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is in accordance with other STE studies in HTN patients with LV hypertrophy [12,13]. Some authors even showed an early impairment of LA reservoir function in the absence of LV hypertrophy [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…The strongest echocardiographic predictor for LA conduit function were E 0 and E/E 0 . STE [12][13][14][15][16] as well as VVI based [10,13] studies have consistently reported decreased conduit function in HTN patients. As an index of early diastole, E/E 0 is affected by LV relaxation abnormalities and by increased filling pressures.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations